Odour qualities and thresholds of physiological metabolites of 1,8-cineole as an example for structure-activity relationships considering chirality aspects - Kirsch, Frauke; Büttner, Andrea (Chemistry & Biodiversity, 2013)
The present study aimed at analyzing the odor properties of a group of physiological human metabolites of the odorant 1,8-cineole: 2,3-dehydro-, α2,3-epoxy-, α/β2-hydroxy-, α3-hydroxy-, 4-hydroxy-, 7-hydroxy-, 9-hydroxy-, 2-oxo-, and 3-oxo-1,8-cineole. These metabolites constitute a group of structurally closely related molecules, which differ mainly in nature and position of O-containing functional groups. They thus offer the possibility to correlate odor properties with molecular structure, i.e., to establish structure odor relationships of compounds that are biologically generated from a potent odorant as parent substance. Generally, the metabolites preserved the eucalyptus-like odor quality of 1,8-cineole but showed additional odor notes such as sweet, citrus-like, plastic-like, earthy, musty, and faecal, which made them distinguishable. The individual enantiomers of chiral molecules also exhibited different odors. With the exception of 2,3-dehydro-1,8-cineole, all metabolites showed a highly decreased odor threshold in comparison to 1,8-cineole. The determination of odor qualities and odor thresholds was accomplished by gas chromatography/olfactometry (GC/O) on achiral and chiral GC capillaries. The results were correlated with common theories on structure - odor relationships.
UnivIS-Import:2015-03-09:Pub.2013.nat.dchph.llmch.odourq
Keywords: 1; 8-Cineole; Metabolites; Gas chromatography/olfactometry; Odor threshold